Telaah Hukum Islam terhadap Asuransi BPJS: Perspektif Maqasid al-Shariah dalam Pelayanan Kesehatan - Rifyan Zahir; Tari Lestari; Kurniati (Jurnal Ilmu Hukum, 2025)
This study aims to analyze the suitability of the Health Social Security Organizing Agency (BPJS) in Indonesia with the principles of Islamic law, especially in the perspective of Maqasid al- Shariah. Maqasid al-Shariah focuses on maintaining the five main aspects of life: religion, soul, mind, offspring, and property. This research uses a qualitative method with a descriptive-analytical approach, which examines aspects of BPJS operations such as contracts, fund management, and penalty policies, as well as their impact on Muslim communities. The research findings show that BPJS Kesehatan can support the Maqasid al-Shariah objectives in protecting the soul (hifz al-nafs) and property (hifz al- mal), but there are some technical aspects that need to be adjusted to sharia principles, such as the late payment penalty mechanism and fund management. In this context, solutions based on tabarru' (grant) contracts, ta'widh (compensation), and the application of waqf as an alternative financing can be steps that are in accordance with Islamic law. This research provides an important contribution to the development of BPJS policies that are more inclusive and fair, while reflecting sharia values in Indonesia's social security system.